Non-Classical 21-Hydroxylase Deficiency: Analysis of a Mutant Gene in a Uyghur Family and Literature Review - Maimaitiming J; Amuti G; TuHuTi A; Chen Y; Song XX; Wang J; Alimu A; Zhang K; Abudounaiyimu M; Jiang J; Wang XL; Guo YY (Dove Medical Press, 2021)
Jimilanmu Maimaitiming,1 Guli Amuti,1 AiHeMaiTiJiang TuHuTi,1 Yuan Chen,1 Xiang-Xin Song,1 Jing Wang,1 Adila Alimu,1 Kaidi Zhang,1 Munila Abudounaiyimu,1 Jun Jiang,2 Xin-Ling Wang,1 Yan-Ying Guo1 1People’ s Hospital of Xinjiang Uygur Autonomous Region, Urumqi, 830001, People’s Republic of China; 2Key Laboratory of Genome Science and Information, Beijing Institute of Genomics, Chinese Academy of Sciences, Beijing, 10029, People’s Republic of ChinaCorrespondence: Yan-Ying Guo; Xin-Ling WangDepartment of Endocrinology, People’s Hospital of Xinjiang Uygur Autonomous Region, No. 91 of Tianchi Road, Tianshan District, Urumqi, 830001, People’s Republic of ChinaTel +86 991 8563546Fax +86 991 8563607Email guoyy8543217@163.com; wangxl52013674@sina.comObjective: The gene mutation and clinical characteristics of a patient with non-classical 21-hydroxylase deficiency and his family were analyzed.Methods: A patient was diagnosed with non-classical 21-hydroxylase deficiency in the Department of Endocrinology of People’s Hospital of Xinjiang Uygur Autonomous Region in December 2016. The clinical data and related gene-sequencing results were analyzed. The detected mutations were verified in nine members of the family.Results: Gene-sequencing results revealed that the proband and the other three members of the family (proband, proband’s mother’s younger brother and the proband’s mother’s younger brother’s younger daughter, and proband’s second elder sister) shared the following mutations: Ile173Asn, Ile237Asn, Val238Glu, Met240Lys, Val282Leu, Leu308Phefs*6, Gln319Ter, Arg357Trp, and Arg484Profs. The Val282Leu mutation was heterozygous in the proband’s mother’s younger brother’s younger daughter, but homozygous in the other three individuals. The father of the proband, the elder brother of the father of the proband, the third younger brother of the father of the proband, and the elder sister of the proband all carried only the Val282Leu mutation.Conclusion: Val282Leu is the gene responsible for non-classical 21-hydroxylase deficiency. Screening for this gene in the offspring of patients with non-classical 21-hydroxylase deficiency may help to identify cases early.Keywords: congenital adrenal hyperplasia, non-classical 21-hydroxylase deficiency, CYP21A2 gene, gene mutation